Economics and marketing of dry fish production in Thoothukudi District, Tamil Nadu, India - Madan, M. S.; Radhakrishnan, Kalidoss; Ranjith, L.; Narayanakumar, R.; Aswathy, N.; Kanthan, K. P. (Indian Journal of Fisheries, 2018)
An attempt has been made to evaluate the economics and marketing of dry fish production in Thoothukudi District of Tamil Nadu, India. The information on various aspects of the dry fish enterprise was collected through random sampling of 29 dry fish producers in a pre-structured interview schedule. The results indicates that 50 % of the total dry fish produced (in terms of quantity) was contributed by sardines and anchovies however, the seer fishes fetched a premium market price of ₹550 kg-1 followed by carangids (₹125 kg-1), and belonids (₹115 kg-1). The dry fish production found to be a profitable business with an Internal Rate of Returns (IRR) value of 75 % and Simple Rate of Returns (SRR) value of 43.48% respectively with a net profit margin of ₹ 2258.83 week-1 was possible. The study also suggests that the dry fishes reached the consumers by way of three marketing channel viz., the channel 1 (producer to consumer) was found the most efficient marketing channel over the channel 2 (producer, middleman and consumer) and channel 3 (producer, wholesaler, middleman and consumer). The cost of raw materials, transportation, packaging, and market margin were the key factors that influences and decides the income of the dry fish producers and all the factors exhibits a statistical significance at 0.05 level.